Turtles all the way down - Green, John, 1977- (New York, NY : Dutton Books, an imprint of Penguin Random House, LLC, 2017)
Sixteen-year-old Aza never intended to pursue the mystery of fugitive billionaire Russell Pickett, but there s a hundred thousand dollar reward at stake and her Best and Most Fearless Friend, Daisy, is eager to investigate. So together, they navigate the short distance and broad divides that separate them from Russell Pickett s son, Davis.
Keywords: Obsessive-compulsive disorder -- Juvenile fiction; Missing persons -- Juvenile fiction; Friendship -- Juvenile fiction; Mystery fiction